The Effect Of Transformation Part In Image Compression - Unan Yusmaniar Oktiawati (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2008)
Image compression is an important part in many signal processing applications to minimize data storage.In the last few years, many experiments of wavelet-based schemes for image compression have been developedand implemented. This paper presents comparison of DCT-based method with wavelet-based image compression.Keywords: Discrete Cosine Transform, Wavelet, Dual Tree Complex Wavelet Transform, Image Compression